Maternal Hypercholesterolemia May Involve in Preterm Birth - Chen, Jingfei; Hua, Lan; Luo, Fei; Chen, Jianlin (Frontiers in Cardiovascular Medicine, 2022)
Maternal hypercholesterolemia during pregnancy is associated with an increased risk of preterm birth which is defined as <37 weeks of complete gestation. However, the underlying mechanism for the association between hypercholesterolemia and preterm birth is not fully understood. Macrophage, as one of the largest cell types in the placenta, plays a very critical role in mediating inflammation and triggers labor initiation. Here, we hypothesize that macrophages can uptake maternal excessive cholesterol leading to its accumulation, resulting in a breach of the immune tolerance and precipitating labor.